Long-term storage of seeds from plant gene pool samples in the National Depository - Chernobai, Yuliia; Riabchun, Viktor; Kuzmyshyna, Nataliia; Shyianova, Tetyana; Chernobai, Serhii (Problems of Cryobiology and Cryomedicine, 2026)
Here, we have explored the viability of plant gene pool samples deposited for long-term storage at the National Depository for Plant Genetic Resources, where 50,743 seed samples from 741 species of 308 crops, originating from 123 countries, are stored at temperatures ranging from –18... –20 °C in sealed foil bags. The intake of samples for long-term storage over the past 24 years has been analyzed by crop group and origin. The dynamics of seed germination rates for various crops was assessed over a 20-year storage period. Among 13 crop groups, namely cereals (28.97%), corn (17.23%), grains (8.87%), legumes (15.53%), oilseeds (5.74%), industrial crops (7.37%), medicinal and essential oil crops (2.00%), forage crops (6.40%), vegetable and melon crops (7.36%), potatoes (0.01%), ornamental flower and herb crops (0.01%), fruit (0.01%), forest and woody ornamental (0.50%) crops, there have been identified the most cold-tolerant species capable of maintaining high germination rates (90–98%) for 15–20 years, as well as the samples with low seed longevity. The research findings are important for extending seed viability during long-term storage in gene banks and for further use in breeding programs. Probl Cryobiol Cryomed. 2026;36(1):32—39